2016
DOI: 10.1038/srep23178
|View full text |Cite
|
Sign up to set email alerts
|

Applications using high-Tc superconducting terahertz emitters

Abstract: Using recently-developed THz emitters constructed from single crystals of the high-Tc superconductor Bi2Sr2CaCu2O8+δ, we performed three prototype tests of the devices to demonstrate their unique characteristic properties for various practical applications. The first is a compact and simple transmission type of THz imaging system using a Stirling cryocooler. The second is a high-resolution Michelson interferometer used as a phase-sensitive reflection-type imaging system. The third is a system with precise temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…As compact solid-state devices, intrinsic Josephson-junction (IJJ) stacks made of the high-criticaltemperature (T c ) superconductor Bi 2 Sr 2 CaCu 2 O 8+δ (BSCCO) have attracted much attention due to their potential to radiate especially at subterahertz frequencies [3][4][5], and intensive experimental and theoretical research has been performed. The possibility to perform terahertz imaging [65][66][67][68] and gas detection [69] or to realize an all-high-T c integrated receiver [70] has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…As compact solid-state devices, intrinsic Josephson-junction (IJJ) stacks made of the high-criticaltemperature (T c ) superconductor Bi 2 Sr 2 CaCu 2 O 8+δ (BSCCO) have attracted much attention due to their potential to radiate especially at subterahertz frequencies [3][4][5], and intensive experimental and theoretical research has been performed. The possibility to perform terahertz imaging [65][66][67][68] and gas detection [69] or to realize an all-high-T c integrated receiver [70] has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The highest degree of circular polarization (DOCP) recorded in the study proposed herein is 99.7%, which is higher than that recorded by state-of-the-art quantum cascade lasers used for obtaining circular polarization [9,10,27]. As circularly polarized THz waves could be employed in a wide variety of potential applications, the result obtained in this study, along with recently reported packaging [28] and demonstration of THz torch [29], it is believed, will significantly influence and inspire the development of practical applications of IJJ-based THz emission devices [4,30].…”
Section: Introductionmentioning
confidence: 58%
“…Later Nakade et al demonstrated a compact and userfriendly transmission THz imaging system (see Fig. 11) using a rectangular stand-alone IJJ THz emitter made by Ar milling as the THz source, a Stirling cryo-cooler engine, two THz lenses, an InSb hot-electron bolometer detector, a lock-in amplifier, two-dimensional scanning stage, an analog to digital converter, a function generator, and a temperature controller [91]. The system could be easily operated down to T= 40 K. They have also developed a home-built Michelson type of interferometer for the realization of phase-sensitive imaging systems.…”
Section: -Transmission Type Imagingmentioning
confidence: 99%
“…To demonstrate the performance of the THz transmission imaging system, two samples, (i) an integrated circuit (IC) card [91] and (ii) a thin razor blade placed inside a brown paper envelope, were considered [40] (see Fig. 12).…”
Section: -Transmission Type Imagingmentioning
confidence: 99%